Analysis of the possibilities and peculiarities of programming cryptology problems on a quantum computer - Каптьол, Є.Ю.; Горбенко, І.Д. (Radiotekhnika, 2020)
This paper is devoted to detailing the possibilities and features of quantum computer use for cryptological problems, their demonstration, justification of approaches to the possibilities analysis and studying features of cryptanalysis problems programming on quantum computers. The possibilities and availability of hardware for solving cryptanalysis problems through quantum methods are analyzed and existing restrictions of their use are determined. The quantum computer and quantum computer programming features are considered. The possibilities of quantum computer use for cryptanalysis are also considered with the Grover’s method example. The essence of Grover’s method and features of its application for cryptanalysis are given. An example of its application to the search space which is represented by a quantum register of 56 qubits is given as well. The quantum computer application of Grover’s method on quantum computer accessible through a loud service is considered. Schemes for conducting a search by Grover's method for quantum computer application are developed, containing a different number of Grover iterations to study the need for executing a full cycle, the possibility to stop and evaluate search results at a certain stage. The developed circuits are tested on quantum computers with different architectures and on a quantum simulator provided for the analysis of circuits intended to run on a quantum computer. The comparison of the expected and obtained results of the Grover’s method application at different search stages on quantum computer is given.